2021
DOI: 10.4018/978-1-7998-7856-8.ch001
|View full text |Cite
|
Sign up to set email alerts
|

Active Blended Learning

Abstract: This chapter focuses on the joint implementation of blended learning and active learning. The authors analysed 152 institutional websites containing definitions of these concepts. Blended learning is commonly, though arguably simplistically, viewed as the combination of face-to-face and online components. Active learning is often described as a pedagogical approach that engages students in higher-order thinking tasks, usually requiring collaboration with others. The authors systematically reviewed the literatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 31 publications
0
15
0
2
Order By: Relevance
“…The authors, between them, manage and teach undergraduate modules as part of the marketing communication curriculum across four undergraduate degrees in Fashion Marketing, Advertising and Digital, Marketing (top up), and Marketing, using Active Blended Learning principles (Armellini & Rodriguez, 2021). These modules include Introduction to Marketing Communications (Level 4), PR Management (Level 5), Integrated Marketing Communications (Level 5), Advertising (Level 6), Advertising Consultancy (Level 6), and Campaign Planning (Level 6).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors, between them, manage and teach undergraduate modules as part of the marketing communication curriculum across four undergraduate degrees in Fashion Marketing, Advertising and Digital, Marketing (top up), and Marketing, using Active Blended Learning principles (Armellini & Rodriguez, 2021). These modules include Introduction to Marketing Communications (Level 4), PR Management (Level 5), Integrated Marketing Communications (Level 5), Advertising (Level 6), Advertising Consultancy (Level 6), and Campaign Planning (Level 6).…”
Section: Methodsmentioning
confidence: 99%
“…This type of student activity and engagement is also referred to as active learning which contrasts with the more traditional lecture approach (Brennan, 2013). The U.K. university in which this research was undertaken is recognized as being the first university to adopt the Active Blended Learning framework as its standard approach to learning and teaching across the whole University which led to the building of a new campus with no lecture halls (Armellini & Rodriguez, 2021). The blended element here has a wider inference than online and face-to-face, as is sometimes made, but types of activities and approaches to assessment adjusted to context and the needs of the students.…”
Section: Teaching Social Media Marketingmentioning
confidence: 99%
“…Currently, there are more and more publications devoted to combined application of AL and BL in engineering education that report its enhanced outcomes and other benefits for students and highlight the usefulness of this association for didactic and pedagogical practices [27,28]. A new active blended learning (ABL) platform has already become the normal mode of knowledge delivery at several universities based on the effective use of the BL and on making the strong and explicit links between online and offline AL activities.…”
Section: Combining the Active Learning And Blended Learning Paradigmsmentioning
confidence: 99%
“…In particular, several challenges of joint implementation of BL and AL are addressed in [27]. Following the analysing of 152 institutional websites containing definitions of these concepts and systematic review of the literature on ABL, the authors found their strong connection and dependence.…”
Section: Combining the Active Learning And Blended Learning Paradigmsmentioning
confidence: 99%
“…O'Dea and Stern, 2021) as well as pedagogical research (e.g. Armellini and Rodriguez, 2021) and institutions (i.e. Advance HE) advocating for a hybrid and/or blended approach to learning.…”
Section: Introductionmentioning
confidence: 99%